Chronic thyroiditis in lateral ectopic thyroid mimicking cervical metastasis of thyroid cancer. (1st July 2021) - Pederzoli, Simone; Salviato, Tiziana; Mattioli, Francesco; Di Massa, Gianluca; Brigante, Giulia
Abstract : Summary: We present the case of a 45-year-old Caucasian woman who attended the Endocrinology Unit for a left cervical mass discovered during follow-up for autoimmune chronic thyroiditis. The ultrasound-guided fine-needle aspiration biopsy of the lesion was consistent with a metastasis of follicular thyroid carcinoma. The sonographic neck evaluation revealed no thyroid nodules but three markedly hypoechoic and highly vascularized areas, with irregular margins and hyperechoic spots. In the clinical suspicion of primary thyroid neoplasm, ultrasound-guided fine-needle aspiration biopsy of two of the three areas was performed, but both cytological reports were non-diagnostic, revealing only colloid and blood. Subsequently, the patient underwent surgical removal of the cervical mass, with the intra-operatory consultation with frozen section examination suggesting follicular-like neoplasia. For this reason, thyroidectomy with both central and lateral neck dissection was performed. Surprisingly, the final histologic examination revealed chronic thyroiditis in the thyroid specimen and no evidence of metastasis in the left neck mass. Consequently, the pathological revision of the frozen section assessment led to the final diagnosis of chronic thyroiditis on the lateral ectopic thyroid. This case represents an uncommon example of lateral ectopic thyroid tissue with coexisting normally located thyroid tissue both affected by chronic thyroiditis. Learning points: Ectopic thyroid must be considered in the diagnostic work-up of lateral neck mass. Even if rare, ectopic thyroid tissue can be found lateral to the carotid sheath and with coexisting normally located thyroid tissue. As the orthotopic tissue, lateral ectopic thyroid tissue can be affected by chronic thyroiditis, which may complicate the diagnosis both on ultrasound and cytology.